Effect of Xanthone Administration on The Number of Sertoli Cells In Mice Induced By 2-Methoxyethanol - Ernawati, Ernawati (NHM PRESS, 2023)
Antioxidants can be used to protect against oxidative stress which is one of the important mechanisms of 2- methoxyethanol (2-ME) -induced testicular toxicity . This research was conducted to find out normal and abnormal motility of spermatozoa cells in mice induced by 2- Methoxyethanol . The study used 35 male mice which were divided into 5 groups, namely: the control group (the mice were given purified water every day by distillation); the 2-ME group (the mice were given 2-ME 200 mg /kg BW daily orally once a day for 35 days); and the treatment group (the mice were given xanthones 60 mg , 120 mg , and 240 mg /kg BW orally once a day for 38 days, and on the 3rd day, 2-ME 200 mg /kg BW were given one hour after. Xanthones were given). After 38 days, the next sperm mice will conduct inspection motility. The results showed that the administration of 2-ME could influence abnormality spermatozoa motility. However, xanthone treatment significantly shows _ enhancement normality spermatozoa motility . Conclusion From the results of this study indicate that xanthones are able to increase spermatozoa motility in mice that were given 2-ME.